Utilization of fly ash and bottom ash to increase the value of unconfined compression strength on subgrade - Woelandari Fathonah; Rama Indera Kusuma; Enden Mina; Restu Wigati; Dwi Esti Intari; Nada Shafa Soraya Gandakusumah (Jurnal Teknika, 2022)
Soil is the most important part to support all traffic loads or construction loads placed on it. Soils that have low bearing capacity, such as clay, need stabilization techniques to increase the carrying capacity of the soil. One of the stabilization techniques is to mix the soil with Fly ash and Bottom ash. The purpose of this study was to determine the effect of Fly ash and Bottom ash on the physical properties of the soil and the value of unconfined compression strength test. The variations of Fly ash and Bottom ash used were Fly ash 0% and 20% and variations of Bottom ash 0%, 10%, 20% and 30% with curing time of 0, 7, 14 and 28 days. Soil is classified according to the Unified Soil Classification System (USCS) method. The results showed that the soil classification was classified as OH, namely organic clay with high plasticity of 21.08%. The results of the unconfined compression strength test show that the addition of fly ash and bottom ash increases the qu value of the clay soil. The optimum qu value was obtained at variation B (Bottom ash 10% and Fly ash 20%) with 28 days curing time of 2,994 kg/cm2. The decrease in the value of qu occurred in variation C (Bottom ash 20% and Fly ash 20%) and variation D (Bottom ash 30% and Fly ash 30%). Soil with the addition of 0% and 20% Fly ash and Bottom ash at variations of 0%, 10%, 20% and 30% showed a decrease in the value of the soil plasticity index from 21.083% to 7.511%.